Cortical–Hypothalamic Integration of Autonomic and Endocrine Stress Responses - Schaeuble, Derek; Myers, Brent (Frontiers in Physiology, 2022)
The prevalence and severity of cardiovascular disease is exacerbated by chronic stress exposure. While stress-induced sympathetic activity and elevated glucocorticoid secretion impair cardiovascular health, the mechanisms by which stress-responsive brain regions integrate autonomic and endocrine stress responses remains unclear. This review covers emerging literature on how specific cortical and hypothalamic nuclei regulate cardiovascular and neuroendocrine stress responses. We will also discuss the current understanding of the cellular and circuit mechanisms mediating physiological stress responses. Altogether, the reviewed literature highlights the current state of stress integration research, as well unanswered questions about the brain basis of cardiovascular disease risk.